Public awareness, specific knowledge, and worry about mpox (monkeypox): A preliminary community-based study in Shenzhen, China - Ren, Fangmei; Liu, Junchao; Miao, Jianping; Xu, Yucheng; Zhang, Ruiyin; Fan, Jingjie; Lin, Wei (Frontiers in Public Health, 2023)
Background The mpox (monkeypox) outbreak has been declared to be a public health emergency of international concern by the Director-General of World Health Organization in July 2022. However, evidence regarding the awareness, knowledge, and worry about mpox in the general population remains scant. Methods A community-based survey targeting community residents was preliminarily conducted in Shenzhen, China in August 2022 by using a convenience sampling method. Information on mpox-related awareness, knowledge, and worry was collected from each participant. Binary logistic regression analyses with the stepwise procedure were applied to explore the factors associated with awareness, knowledge, and worry about mpox. Results A total of 1028 community residents were included in the analysis (mean age: 34.70 years). Among these participants, 77.9% had ever heard of mpox, and 65.3% were aware of the global outbreak of mpox. However, only about half of them had a high level of knowledge regarding mpox (56.5%) and related symptoms (49.7%). More than one-third of them (37.1%) expressed a high level of worry about mpox. Having high knowledge levels of mpox and related symptoms were positively associated with a high level of worry (OR: 1.79, 95%CI: 1.22~2.63 for a single high knowledge level; OR: 1.98, 95%CI: 1.47~2.66 for both high knowledge levels). Conclusions This study identified the gaps in public awareness and specific knowledge of mpox in Chinese people, providing scientific evidence for the prevention and control network of mpox at the community level. Targeted health education programs are of urgent need, which should be implemented along with psychological interventions to release public worry if necessary.